Seafood safety, processing, and biotechnology (Technomic Pub., 1997)
Research and development of seafood continues to be productive in terms of new and improved products for both food and non-food purposes. The use of biotechnology, microbiology, computer modeling and advanced analytical techniques has led to improvements in processing and product safety. This recent book provides extensive new information on these developments. The 25 reports were prepared by food scientists specializing in seafood. The reports are well illustrated with numerous schematics and some micrographs. Extensive reference data is provided in tables and graphs.